National Health Research Systems in the WHO African Region: current status and the way forward - Kirigia, Joses Muthuri; Ota, Martin Okechukwu; Motari, Marion; Bataringaya, Juliet Evelyn; Mouhouelo, Pascal (Health research policy and systems, 2015)
A number of resolutions of the World Health Assembly and the WHO Regional Committee for Africa call upon African countries and their development partners to make the required investments in national health research systems (NHRS) to generate knowledge and promote its use in tackling priority public health challenges. Implementation of these resolutions is critical for Africa to progress with the rest of the world in achieving the post-2015 health sustainable development goal. This study assesses the current status of some NHRS components in the 47 countries of the WHO African Region, identifies the factors that enable and constrain NHRS, and proposes the way forward.
Keywords: Production and use; National health research systems; Creating and utilizing resources; Financing; Governance of research for health